2011
DOI: 10.1016/j.ccr.2010.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Carcinomas Arise from Hair Follicle Stem Cells in Ptch1+/− Mice

Abstract: SUMMARY Basal cell carcinomas (BCCs) are hedgehog-driven tumors that resemble follicular and interfollicular epidermal basal keratinocytes and hence long have been thought to arise from these cells. However, the actual cell of origin is unknown. Using cell fate tracking of X-ray induced BCCs in Ptch1+/− mice, we found their essentially exclusive origin to be keratin 15-expressing stem cells of the follicular bulge. However, conditional loss of p53 not only enhanced BCC carcinogenesis from the bulge but also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(181 citation statements)
references
References 67 publications
5
174
1
1
Order By: Relevance
“…The first two models also show different preferences for tumor initiation in the IFE vs. the HF, although the K5tTA and K5Cre*PR1 transgenes are driven by the same bovine K5 promoter sequence (14,15,28), and the different compartments of the HFs and the IFE are uniformly targeted (14). This and two recent studies argue for differential sensitivity of epidermal cell subpopulations to the activation of Hh signaling by targeting specific pathway components (29,30). Our data show that the bulge SC compartment, marked by expression of CD34, is largely unaffected in the Lgr5-EGFP-IRES-creER T2 /Ptch1 fl/fl model, and that cells present in early lesions exhibit an Lgr5+/CD34− staining pattern suggesting the SHG as a likely source of tumor-initiating cells in the wound areas of these mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The first two models also show different preferences for tumor initiation in the IFE vs. the HF, although the K5tTA and K5Cre*PR1 transgenes are driven by the same bovine K5 promoter sequence (14,15,28), and the different compartments of the HFs and the IFE are uniformly targeted (14). This and two recent studies argue for differential sensitivity of epidermal cell subpopulations to the activation of Hh signaling by targeting specific pathway components (29,30). Our data show that the bulge SC compartment, marked by expression of CD34, is largely unaffected in the Lgr5-EGFP-IRES-creER T2 /Ptch1 fl/fl model, and that cells present in early lesions exhibit an Lgr5+/CD34− staining pattern suggesting the SHG as a likely source of tumor-initiating cells in the wound areas of these mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that either the microenvironment of IFE is more permissive or that following migration to the IFE (Kasper et al 2011) bulge SCs are reprogrammed into an IFE fate, which is required to allow the oncogenic program dictated by HH signaling. Genetic lineage-tracing experiments followed by ionizing radiation suggested that bulge SCs could be the cellular origin of ionizing radiation-induced BCC (Wang et al 2011). However, the infundibulum and IFE-ectopic activity of the K15CREPR, the K15 expression in BCC , and the leakiness of K15CREPR (Lapouge et al Figure 5.…”
Section: Regulation Of Skin Stem Cellsmentioning
confidence: 99%
“…The E6 and E7 oncoproteins may contribute to tumor initiation and play important roles in malignant progression through the induction of genomic instability and other mechanisms (24). The complete loss of p53 was shown to result in upregulated expression of the hedgehog pathway, with activated pathway being a prerequisite for the development of BCC (25). Our data may indicate that loss of p53 by E6 of HPV-18 promotes the development of advanced-stage BCC even without UVB exposure.…”
Section: Discussionmentioning
confidence: 71%